Pequenas barragens: uma oportunidade de desenvolvimento científico, técnico e regulamentador - NAVA, Francy Rosy (Universidade Federal do Pará, 2020)
Although small water track dams have important and various purposes, even if they are smaller they are structures that causes considerable socio-environmental changes and represent increasingly evident risks. These terms are not considered by normative directives established in Brazil. That is why the regulatory system has been stimulated by strong discussions in analysis on advantages and disadvantages of the dams, only directed towards the great enterprises. Thus, a gap has been created, which substantiates and directs this study in the sense that the small water dams also deserves attention. To prove this need, this research was guided by the following scientific questions: 1. How the occurrence of small dams are addressed in scientific and technical environment? 2. What is the representativeness of the impacts events associated with the construction / operation of small dams? 3. How does the legal and institutional system incorporate the management of small dams? In order to answer them, a methodological route was established, allowing the purpose to analyzing small water track barriers in the Uraim river basin under the perspective of territorial and socio-environmental management and normative systems. The results demonstrated several weaknesses in scientific and technical knowledge, as well as in the normative and institutional ordering responsible for the environmental management of structures with polluting / degrading potential. The weakness found, whether in licensing or safety aspects are the main factors that drive the practice of establishing small irregular barriers in water tracks, disregarding technical and environmental criteria. It was also verified the representativeness of small dams and the significant socio-environmental risks. In this way, this study contributes to in-depth understanding of the roles of all actors responsible for the management of small dams. In addition, stimulates discussion on the performance of normative and institutional planning in promoting the efficient implementation of the environmental policies established by the government. These results can be used by policymakers and government decision-makers to improve the regulatory framework and executor role.